2022
DOI: 10.3390/biomedicines10081956
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Roles of Ceramide in the Progression and Pathogenesis of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most common neurodegenerative disorder, and is associated with several pathophysiological features, including cellular dysfunction, failure of neurotransmission, cognitive impairment, cell death, and other clinical consequences. Advanced research on the pathogenesis of AD has elucidated a mechanistic framework and revealed many therapeutic possibilities. Among the mechanisms, sphingolipids are mentioned as distinctive mediators to be associated with the pathology of AD. Reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 101 publications
1
9
0
Order By: Relevance
“…In addition, an accumulation of Cer in the mitochondria increases the permeability of the outer mitochondrial membrane and stimulates the release of some pro-apoptotic proteins . This mitochondrial Cer accumulation has been previously observed in the pathogenesis of other diseases such as type 2 diabetes or Alzheimer’s disease . While it is not possible to confirm the accumulation of Cer in the mitochondria, given the changes observed in the pathogenesis of Long COVID, this approach aligns more closely with the observed results, Figure .…”
Section: Discussionsupporting
confidence: 87%
“…In addition, an accumulation of Cer in the mitochondria increases the permeability of the outer mitochondrial membrane and stimulates the release of some pro-apoptotic proteins . This mitochondrial Cer accumulation has been previously observed in the pathogenesis of other diseases such as type 2 diabetes or Alzheimer’s disease . While it is not possible to confirm the accumulation of Cer in the mitochondria, given the changes observed in the pathogenesis of Long COVID, this approach aligns more closely with the observed results, Figure .…”
Section: Discussionsupporting
confidence: 87%
“…Following 26 weeks of training, increases in PUFA and lysophospholipids, and decreases in ceramides, sphingolipids and phospholipids were observed. Ceramides and sphingolipids have previously been proposed as AD biomarkers and linked to cognitive function and mood regulation [ 31 , 32 ]. Thus, systemic metabolite markers that can assess the effects of exercise on AD-related outcomes offer potential for insights in disease progression, and development of therapeutics.…”
Section: Metabolomics In Exercise Biomedicinementioning
confidence: 99%
“…In the early stages of AD, there is an observed deficiency in multiple glucosides and elevated Cer in the lesion area ( Han et al, 2002 ). Lipidomics studies have revealed a threefold increase in ceramide levels in the brains of AD patients compared to healthy controls ( Chowdhury et al, 2022 ; Reveglia et al, 2023 ). Elevated plasma ceramide and sphingomyelin levels have also been found in AD patients and have been proposed as diagnostic markers for these diseases ( Olsen and Færgeman, 2017 ).…”
Section: The Pathogenesis Of Ceramide and Admentioning
confidence: 99%